Earthquake Prediction by Seismic Electric Signals The success of the VAN method over thirty years - Lazaridou-Varotsos, Mary S. (Springer Praxis Books, 2013)
As evidenced dramatically and tragically in 2011 alone,earthquakes cause devastation and their consequences in terms of human suffering and economic disaster can last for years or even decades. The VAN method of earthquake prediction, based on the detection and measurement of low frequency electric signals called Seismic Electric Signals (SES), has been researched and evaluated over 30 years, and now constitutes the only earthquake prediction effort that has led to concrete successful results. This book recounts the history of the VAN method, detailing how it has developed and been tested under international scrutiny. Earthquake Prediction by Seismic Electric Signals " describes, step by step, the development of the VAN methodsince1981; " explains both the theoretical model underpinning the research and the physical properties of SES; " analyzes the SES recordings and the prediction for each major earthquake in Greece over the last 25 years; " introduces a new time domain, natural time, which plays a key role in predicting impending catastrophic events.